2018
DOI: 10.1111/jonm.12662
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in nursing: The role of internal and external factors

Abstract: Recent evidence shows that resilience can buffer the negative impact of workplace stressors on nurses and is linked to favourable patient outcomes. However, the comparative effectiveness of different contributing factors to nurses' resilience has not yet been examined. Our objective was to examine and compare the impact of individual characteristics, external factors and coping strategies on nurses' resilience. A descriptive cross-sectional study was conducted. Data were collected from 1,012 Greek nurses worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 49 publications
2
66
1
5
Order By: Relevance
“…Resilience helps medical workers recover better from trauma, which may help explain why resilient medical workers have lower anxiety and depression in the face of public health emergencies. Consistent with our study, analysis of more than 1000 nurses in Greece suggested that greater resilience was associated with lower anxiety [ 22 ]. In a study of Toronto-based health care workers who continued to work in hospitals one to 2 years after the SARS outbreak, incidence of new episodes of psychiatric disorders were similar to or lower than community incidence rates [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…Resilience helps medical workers recover better from trauma, which may help explain why resilient medical workers have lower anxiety and depression in the face of public health emergencies. Consistent with our study, analysis of more than 1000 nurses in Greece suggested that greater resilience was associated with lower anxiety [ 22 ]. In a study of Toronto-based health care workers who continued to work in hospitals one to 2 years after the SARS outbreak, incidence of new episodes of psychiatric disorders were similar to or lower than community incidence rates [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…In other words, participants who scored higher on resilience showed a lower score on anxiety and depression. Data collected from 1,012 Greek nurses suggested that resilient nurses had lower anxiety [20]. In a study among health care workers in Toronto, incidence of new episodes of psychiatric disorders after the SARS outbreak were similar to or lower than community incidence rates, which may indicate the resilience of medical workers who continued to work in hospitals one to two years after the SARS outbreak [21].…”
Section: Discussionmentioning
confidence: 98%
“…As such, building resilience in risk-elevated and demanding settings has been proposed as an effective way to enhance employee well-being [10][11]. High resilience has been closely linked to reduced burnout and lower nurse turnover [10][11][12]. Additionally, research on resilience has highlighted its role in improving quality of care and enhancing patient satisfaction [9].…”
Section: Introductionmentioning
confidence: 99%
“…clinical settings, social network), and demographic variables (e.g. age, years of experience) [12][13]. However, job satisfaction ranks among the most signi cant factors that contribute to resilience [14].…”
Section: Introductionmentioning
confidence: 99%